The effect of Porphyromonas gingivalis induction on neutrophil’s superoxide production - Nahdiya Fitriyana; Yuliana MD Arina; Happy Harmono; IDA Susilawati (Journal of Dentomaxillofacial Science, 2013)
Microbicidal mechanism with producing free radical superoxide is one of neutrophil response to the bacterialinvasion. When overproducted, the free radical superoxide greater than antioxidan defense system and destroyed thecell itself. P.gingivalis had been knowed as the major bacteria that induce periodontal inflammation. These bacteriacan stimulated neutrophil activities. This was aimed to determinate the superoxide production from neutrophilstimulated with P.gingivalis. Neutrophil as samples were isolated from subject who fulfill the selected criteria. Theintracelluler superoxide production was determinated by nitroblue tetra zolium (NBT)test and the extracellulerproduction by spectrophotometer with wave length 580 nm. The result showed there was superoxide production fromneutrophil stimulated by P.gingivalis. It was concluded that the stimulation of P.gingivalis on neutrophil can promotesuperoxide production both intracelluler and extracelluler.